Diminished neutralizing activity against the XBB1.5 strain in 55.9% of individuals post 6 months COVID-19 mRNA booster vaccination: insights from a pseudovirus assay on 1,353 participants in the Fukushima vaccination community survey, Japan - Zhao, Tianchen; Tani, Yuta; Makino-Okamura, Chieko; Takita, Morihito; Yamamoto, Chika; Kawahara, Eiki; Abe, Toshiki; Sugiura, Sota; Yoshimura, Hiroki; Uchiyama, Taiga; Yamazaki, Isato; Ishigame, Harumichi; et al. (Frontiers in Immunology, 2024)
This study investigates the neutralizing activity against the XBB1.5 variant and the ancestral strain in a population post-bivalent vaccination using a pseudo virus assay validated with authentic virus assay. While bivalent booster vaccination and past infections enhanced neutralization against the XBB 1.5 strain, individuals with comorbidities showed reduced responses. The study suggests the need for continuous vaccine updates to address emerging SARS-CoV-2 variants and highlights the importance of monitoring real-world immune responses.